2023
DOI: 10.2205/2023es000838
|View full text |Cite
|
Sign up to set email alerts
|

Linear perturbations of the Bloch type of space-periodic magnetohydrodynamic steady states. II. Numerical results

R Chertovskih,
V Zheligovsky

Abstract: We consider Bloch eigenmodes of three linear stability problems: the kinematic dynamo problem, the hydrodynamic and MHD stability problem for steady space-periodic flows and MHD states comprised of randomly generated Fourier coefficients and having energy spectra of three types: exponentially decaying, Kolmogorov with a cut off, or involving a small number of harmonics (“big eddies”). A Bloch mode is a product of a field of the same periodicity as the perturbed state and a planar harmonic wave, exp(iq · x). Such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For instance, the kinematic dynamo problem for a parity-invariant flow, for which Table 1. Instances of branching found numerically in [Chertovskih and Zheligovsky, 2023b]. F: figures ibid.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…For instance, the kinematic dynamo problem for a parity-invariant flow, for which Table 1. Instances of branching found numerically in [Chertovskih and Zheligovsky, 2023b]. F: figures ibid.…”
Section: Discussionmentioning
confidence: 98%
“…We have developed a power series asymptotic expansion in ϑ = (η 0 − η) 1/2 of magnetic Bloch modes, kinematically generated by a parity-invariant flow and featuring locally maximum growth rates, which stem from the branch of neutral (i.e., associated with the zero eigenvalue of the magnetic induction operator D (8)) space-periodic modes for q = 0 (see Fig. 14 in [Chertovskih and Zheligovsky, 2023b]). We have shown that branching occurs at a critical molecular diffusivity η 0 for which the two eigenvalues of the operator of eddy diffusivity are imaginary and complex-conjugate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations